83‐4: Investigation on Quantitative Simulation Method of ITO index matrix. Issue 1 (30th May 2018) - Bao-ran, Li; Hong, Yang; Xi-bin, Shao; Zong-jie, Guo; Tao-feng, Xie; Wen-jin, Fan; Qing-pu, Wang; Ling-yan, Wu
Abstract : In view of the fact that the effect of ITO index matrix simulation cannot be obtained directly and accurately in the past research, this paper establishes an ITO IMQS (index matrix quantitative simulation) model in human vision. The ITO IMQS model can be used to obtain the data and pictures of characterization effect of index matrix directly which is based on the theory of the Radiation energy flux and Luminous flux. According to the consequence of calculation and comparison, the model simulation results with the actual situation is consistent, fully shows highly validity of the model. The ITO IMQS model completely solves the problem of ITO index matrix in the early stage of product design, and it also provides great convenience for the timely and effective improvement scheme of the products already in question.